Occurrence and Quantification of escherichia coli and escherichia coli O157:H7 on Conventional Vegetables at Farm Level - Sea, Lillian Shun Yi (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Escherichia coli 0157:H7 is the predominant pathogen in the EHEC group which often implicated in human infections worldwide. The recent outbreaks were frequently linked to the consumption of vegetables, instead of solely on meat and poultry products. The aim of this study is to investigate the prevalence and frequency of E. coli and E. coli 0157:H7 on different types of conventional vegetables from two farms by using the combination ofMPN and PCR. Another goal is to determine the antibiotic susceptibility profile among the E. coli isolates. A total of II types of conventional vegetables including Chinese flowering green, Chinese white stem, water spinach, spinach, Chinese broccoli, Chinese chives, okra, French beans, long beans, sweet potato leaves, and weet leaves in Kuching, Malaysia were investigated. The estimated quantity of E. coli isolates in all samples is more than 1100 MPN/g and the overall CFU/g in all samples ranged from 8.8 x 107 to 1.9 X 106 CFU/g. A full set of target genes for E. coli 0157:H7 was not detected in the samples, but Chinese flowering green and Chinese white stem samples showed the presence of other type of EHEC. Twelve E. coli isolates were subjected to antibiotic susceptibility testing, chloramphenicol and nitrofurantoin were the most effective antibiotic; whereas, cephalothin showed that highest antibiotic resistance. Overall antibiotics resistance pattern of all isolates displayed 1 to 2 resistance patterns with multiple antibiotic resistance (MAR) index ranging from 0 to 0.25 respectively. Hence, the present study indicated that high prevalence of E. coli was detected in conventional vegetables, posing a potential risk for raw vegetable consumption in Malaysia.